The Winning Ticket: An Evaluation of State Regulation of Sports Gambling - Elijah Bunde (Washington University Journal of Law and Policy, 2023)
In 2018, the Supreme Court struck down the Professional and Amateur Sports Protection Act (PASPA) with its decision in Murphy v. NCAA. PASPA prevented states from authorizing gambling on professional and amateur sporting events. States have responded with a diverse range of legislative and regulatory approaches; some states play an active role through state-run gambling platforms while others permit sports betting in the private market. This Note will propose a framework of sports betting policies for state legislatures to enact. The Author first provides historical context for the development of sports betting in the United States. Next, the Author explains the origins and evolution of PASPA and how the issue in Murphy developed over time. Finally, the Author examines different approaches to legalized sports betting in five different states in order to develop an optimal set of gambling laws and policies. Ultimately, the Author advocates for a system of private operation of sports betting with state regulation, strict licensing requirements, legalized mobile betting, and minimal involvement by sports leagues. This Note argues that the proposed framework will benefit state economies, maximize consumer experience, and protect the integrity of sports betting and the sporting events on which wagers are being placed.
Keywords: sports gambling; state regulation; PASPA; Murphy; NCAA; legalized; sports betting; mobile betting; sports leagues; gambling laws; gambling; state economies; integrity; sporting events; wagers; private operation; case study